Identify the therapeutic role and potential mechanism of α-cyperone in diminished ovarian reserve based on network pharmacology, molecular docking, Lip-MS and experimental validation - Guo, Jingwen; Yang, Xitang; Chen, Xue; Hu, Rong; Guo, Hua (Frontiers in Pharmacology, 2026)
BackgroundThe presence of diminished ovarian reserve (DOR) poses a significant threat to female fertility, with no current effective treatment available. Inflammation plays pivotal roles in the pathogenesis of DOR. α-Cyperone (AC) exhibits notable anti-inflammatory and anti-oxidative properties; however, its potential for improving DOR remains unexplored.MethodsThe PubChem, PharmMapper, and SwissTargetForecast databases were queried to retrieve biochemical information and drug targets for AC. The identification of disease targets for DOR involved referring to the OMIM and Genecards databases. AC’s therapeutic targets against DOR were determined by examining the overlap between drug targets and disease targets. To analyze GO function enrichment, KEGG pathway, and disease association, the Metascape database was utilized. The results were then visualized using Cytoscape software. Receptor-ligand interaction between AC and target sites was validated through molecular docking investigations utilizing Pymol and AutoDock program software. The effect of AC on granule cell function was verified in CTX-induced DOR granule cell model. The actual AC-binding proteins in the cells were identified by Lip-MS, and the effects of AC on target protein genes were verified by RT-qPCR.ResultsFollowing the integration of 466 drug targets with 1,529 disease targets, we identified 257 AC targets for the treatment of DOR. We recorded the top 20 enriched biological processes, molecular functions, and KEGG pathways that potentially contribute to the anti-DOR effect of AC. Employing the MCC algorithm, we identified key TOP22 proteins. The docking studies revealed that AC binds strongly to all 22 proteins studied. The CTX-induced DOR granule cell model was successfully established, which was verified by detecting the levels of AMH, ROS, MMP and cell viability, indicating that AC enhanced the function of DOR granule cells. The abnormal expression patterns of MAP2K1, AKT1, ESR2, ERBB2, CDH1, CYP19A1, ESR1 and MAPK8 genes were also reversed. In addition, the binding of AC to MAP2K1, GSK3B and MAPK14 was verified by Lip-MS experiments.ConclusionAC can improve CTX-induced KGN proliferation and improved the function of KGN cell. The mechanism may be due to the targeted binding ability of AC to domains of MAP2K1, MAPK14 and GSK3B. AC’s potential therapeutic targets are comprehensively explored in this study, as well as theoretical support for its use in the treatment of DOR is provided.